How Does COVID-19 Affects Income, Loss of Productivity and Quality of Life among Malaysian? - Ruslan, Noraini (Enhanced Knowledge in Sciences and Technology, 2022)
The COVID-19 pandemic has caused unparalleled magnitude and effect to the rest of the world. The situation in Malaysia is inflamed by the sudden change of Government in early March of 2020. Despite the fact that civilization has been affected by numerous pandemics in the past, it is impossible to predict the long-term economic, behavioral, or sociological effects of COVID-19 due to strict lockdown (Movement Control Order) implementation. A series of questions were administered to understand the impact of COVID-19 on income, loss of productivity and quality of life among 100 Malaysian people across various state. Findings indicated the outbreak of COVID-19 had cause major loss to the economic, health and lifestyle productivity of all respondents, in which, 98% respondents preferred to stay at home rather than being outside due to COVID-19 and 74% were agreed that COVID-19 vaccination make them feel safe. Due to its unpredictable impact, majority of respondents were willing to pay insurance ranging from RM101-RM200 to get good compensation from their loss. This results suggest, a good compensation and insurance action plan could be implemented accordingly in COVID-19 recovery action plan due to the potential for large numbers of people to be adversely affected in economics, social and life productivity.